Laser Filament Induced Water Condensation - Kasparian J.; Webe K.; Vogel A.; Petit Y.; Lüder J.; Hao Z.Q.; Rohwetter P.; Petrarca M.; Stelmaszczyk K.; Henin S.; Wöste L.; Wolf J.-P. (EPJ Web of Conferences, 2013)
At relative humidities above 70%, femtosecond laser filaments generate aerosol particles and water droplets in the atmosphere. The water vapour condensation and droplet stabilization are assured by soluble species produced in the laser plasma.